Influence of body position during Heimlich maneuver to relieve supralaryngeal obstruction: a manikin study - Ichikawa, Michitaro (Acute Med Surg, 2017)
AIM: To study the most effective body position for Heimlich maneuver. METHODS: A choking simulation manikin was connected to a laryngeal model of a child or an adult, and a differential pressure transducer recorded the airway pressure and waveform during the maneuver. A konjac jelly was placed on the larynx to mimic complete supralaryngeal obstruction. The maneuver (five successive compressions) was carried out six times each in standing, prone, and supine positions. For cases of children, we added a supine position with a pillow under the back. RESULTS: In the adult model, airway obstruction was more frequently relieved in the supine and prone positions than in the standing position (P < 0.001). In the child model, airway obstruction was more frequently relieved in the supine position, with a pillow, and in the prone position, than in the standing position (P < 0.001). Without relief, successive Heimlich maneuvers made the airway pressure increasingly negative (adult, from −21.9 ± 6.5 cmH(2)O to −31.5 ± 9.1 cmH(2)O in the standing position [P < 0.001]; child, from −15.0 ± 9.5 cmH(2)O to −30.0 ± 9.2 cmH(2)O in the standing position [P < 0.001] and from −35.0 ± 17.4 cmH(2)O to −47.3 ± 25.1 cmH(2)O in the supine position without a pillow [P = 0.002]). CONCLUSIONS: The Heimlich maneuver was more effective in the supine and prone positions. In children, the prone position may be most effective. Successive Heimlich maneuvers may be harmful when the airway is not relieved after the first compression.